Can previous acid etching increase the bond strength of a self-etching primer adhesive to enamel? - Carvalho,Ana Paula Morales Cobra (2009)
Because a greater research effort has been directed to analyzing the adhesive effectiveness of self etch primers to dentin, the aim of this study was to evaluate, by microtensile testing, the bond strength to enamel of a composite resin combined with a conventional adhesive system or with a self-etching primer adhesive, used according to its original prescription or used with previous acid etching. Thirty bovine teeth were divided into 3 groups with 10 teeth each (n= 10). In one of the groups, a self-etching primer (Clearfil SE Bond - Kuraray) was applied in accordance with the manufacturer's instructions and, in the other, it was applied after previous acid etching. In the third group, a conventional adhesive system (Scotchbond Multipurpose Plus - 3M-ESPE) was applied in accordance with the manufacturer's instructions. The results obtained by analysis of variance revealed significant differences between the adhesive systems (F = 22.31). The self-etching primer (Clearfil SE Bond) presented lower enamel bond strength values than the conventional adhesive system (Scotchbond Multipurpose Plus) (m = 39.70 ± 7.07 MPa) both when used according to the original prescription (m = 27.81 ± 2.64 MPa) and with previous acid etching (m = 25.08 ± 4.92 MPa).